Payback in death - Robb, J. D., 1950- (Robb, J. D., 1950- In death novel, 2023)
"Lt. Eve Dallas is just home from a long overdue vacation when she responds to a call of an unattended death. The victim is Martin Greenleaf, retired Internal Affairs Captain. At first glance, the scene appears to be suicide, but the closer Eve examines the body, the more suspicious she becomes. An unlocked open window, a loving wife and family, a too-perfect suicide note--Eve's gut says it's a homicide. After all, Greenleaf put a lot of dirty cops away during his forty-seven years in Internal Affairs. It could very well be payback--and she will not rest until the case is closed"--